2020
DOI: 10.18196/jrc.1428
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Simple and Low-cost Smartphone Gimbal with MPU-6050 Sensor

Abstract: This paper discusses about design and development of gimbal smartphone, which are made to be simple and less money consuming by utilizing microcontroller and MPU 6050 sensor. Recently, the development of videography and image processing is inseparable from the rapid advance in smartphone technology. One of the most popular features is camera. Hand movements and shocks cause fewer maximum results. To improve the quality of camera captures and video, it is necessary to have a stabilizer for camera position. Thus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 18 publications
0
6
0
3
Order By: Relevance
“…Rafiq et al [20] used the same MPU6050 module to detect the tilting angles in the development of the smartphone gimbal. Zhang et al [21] showed the implementation of IMU for outdoor applications where estimation of absolute attitude is compared with a kinematic model of motion, while Albaghdadi and Ali [22] introduced detailed methods to overcome measurement error caused by vibration when using the MPU6050 module.…”
Section: Platform Testing Methodsmentioning
confidence: 99%
“…Rafiq et al [20] used the same MPU6050 module to detect the tilting angles in the development of the smartphone gimbal. Zhang et al [21] showed the implementation of IMU for outdoor applications where estimation of absolute attitude is compared with a kinematic model of motion, while Albaghdadi and Ali [22] introduced detailed methods to overcome measurement error caused by vibration when using the MPU6050 module.…”
Section: Platform Testing Methodsmentioning
confidence: 99%
“…The master device is a wearable device made with the idea of sensors on arm to make the whole system compact and portable. Different types of microcontrollers are available that help to design and develop low-cost robots [27][28][29]. The environment can be visualized on screen.…”
Section: A Master Devicementioning
confidence: 99%
“…Accordingly, the genetic algorithm often provides a reasonable balance between the PID controller coefficient's accurate values and better PID response regarding the rise time and the settling time. GA consists of four main stages (initial generation, cost function, selection techniques, crossover, and mutation [34], [35].…”
Section: Pid Controller Tuningmentioning
confidence: 99%